2016
DOI: 10.14214/sf.1546
|View full text |Cite
|
Sign up to set email alerts
|

Load level forwarding work element analysis based on automatic follow-up data

Abstract: Highlights• Recent developments in on-board technology enables automatic collection of follow-up data on forwarder work.• Time consumption per load was more strongly associated with Loading drive distance than with extraction distance, indicating that the relevance of extraction distance as a main indicator of forwarding productivity should be re-considered.• Data, within variables, were positively skewed with a few exceptions with normal distributions. AbstractRecent developments in on-board technology have e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
49
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 18 publications
3
49
1
Order By: Relevance
“…In this scenario, the understanding of the forwarding operation is decisive for good planning of the thinning operation in different sites. Forwarding is a complex activity, consisting of several work elements, each of them affected by several factors (Nieminstö et al 2012, Manner et al 2016a, Berg et al 2017. The theoretical analysis and operation planning are intrinsically dependent on the existence of precise time and productivity models (Nurminen et al 2006, Lindroos andWästerlund 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this scenario, the understanding of the forwarding operation is decisive for good planning of the thinning operation in different sites. Forwarding is a complex activity, consisting of several work elements, each of them affected by several factors (Nieminstö et al 2012, Manner et al 2016a, Berg et al 2017. The theoretical analysis and operation planning are intrinsically dependent on the existence of precise time and productivity models (Nurminen et al 2006, Lindroos andWästerlund 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The productivity of forest extraction with forwarders depends on timber volume by load and the cycle time consumption (Nurminen et al 2006). For the purpose of the analysis, the forwarding cycle can be divided into five work elements: driving empty, loading, driving while loading, driving loaded and unloading (Manner et al 2016a). Other activities can be considered, including driving empty on the road and driving loaded on the road.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The steering principles of CBC and IBC are described in Section 2.1. Manner et al (2017) found that using IBC, instead of CBC, improves the crane-work productivity of beginner-level operators (i.e. students at vocational school) because of the improved crane manoeuvrability provided by IBC.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the crane work is the most time-consuming work element (Kellogg and Bettinger 1994;Nurminen et al 2006;Manner et al 2016b). Though, relative time consumption distribution between the work elements depends on extraction distance, assortment-specific log concentrations (expressed e.g.…”
Section: Introductionmentioning
confidence: 99%